2009
DOI: 10.1016/j.jcin.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stent Fracture on the Long-Term Patency in the Femoro-Popliteal Artery

Abstract: Stent fracture worsened the patency during the first 2 years, but it did not apparently affect patency beyond 2 years. In particular, complete stent separation did not affect patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 15 publications
3
71
1
Order By: Relevance
“…Exercise habits have been reported to be associated with stent fracture. 20 It has been reported that stent fracture is associated with re-stenosis. 21 This may explain the higher stent fracture rate in the re-stenosis group observed here, because younger people are more likely to be active than older people.…”
Section: Suzuki K Et Almentioning
confidence: 99%
“…Exercise habits have been reported to be associated with stent fracture. 20 It has been reported that stent fracture is associated with re-stenosis. 21 This may explain the higher stent fracture rate in the re-stenosis group observed here, because younger people are more likely to be active than older people.…”
Section: Suzuki K Et Almentioning
confidence: 99%
“…The 12-month results of the STELLA PTX registry, with TASC C and D femoropopliteal lesions (mean length 252 mm ± 90 mm) and paclitaxel eluting stents (mean number of stents 2.9), revealed a primary patency rate of 52.5 % with an incidence of 25 % in-stent re-stenosis and a stent fracture rate of 12,5 % on a limb basis and 9 % on a per stent basis [16]. It should also be mentioned that other data report the impact of stent fractures on long-time patency rates and clinical outcome remains less clear [17] or rather low [18].…”
Section: Discussionmentioning
confidence: 96%
“…Patency at 12 months reduced from 84.3% to 41.1% in lesions with fractured stents [10]. Iida et al [11] reported the factors associated with stent fracture were longer lesion length, larger number of stents used, and exercise. In our case, the patient underwent implantation with three stents, with a total length of 300 mm, and the patient's exercise adherence was high.…”
Section: Discussionmentioning
confidence: 99%